Physical cues enhancing tissue engineering : from cellular commitment to vascular induction - Fu, Jiayin (2017)
The behaviors of cells, such as survival, proliferation, differentiation, migration, can produce important physical cues, which lead to the occurrence of some important biological processes. In addition, cells are in close contact with extracellular matrix (ECM) in vivo, either continuously or at some important stages of development. ECM is a three-dimensional (3D) protein scaffold and the physical signals from ECM (stiffness and structure) can also affect cell behaviors. In this thesis, we promoted vascularization of tissue constructs and cardiac differentiation of ESCs through manipulation of cell-induced or biomaterial-derived physical signals. We verified the feasibility of using PLGA nanoparticles to label and track ESC status during EB development. The unique cell viability monitoring function of the nanoparticles allowed clear presentation of live cell distribution within EBs, which had high potential to be a powerful tool to screen EBs with comparable sizes. In addition, we successfully imitated some critical aspects of cartilage hypertrophy using in vitro engineered living cartilage templates and osteogenic treatment. Osteogenic treatment induced cartilage hypertrophy and creates channels for vascular invasion in LhCG constructs when implantation in vivo. Hypertrophic transition of LhCG constructs using osteogenic treatment may contribute to the establishment of an in vitro cartilage hypertrophy model that mimic initial stage of endochondral ossification. Besides manipulation of cell behavior-origin physical signals, stiffness and topography of biomaterials were also controlled. Gelatin-dopamine was synthesized for PDMS surface coating. Compared with gelatin, gelatin-dopamine coating reduced hydrophobicity and increased protein adsorption on the PDMS surface. In addition, the gelatin-dopamine coated PDMS surface greatly improved ESC adhesion, proliferation and pluripotency maintenance as compared to gelatin-coated surfaces. ESC-derived EBs also showed increased adhesion and facilitated myocardial differentiation on the gelatin-dopamine coated PDMS surface. These results demonstrated that gelatin-dopamine coating could effectively improve PDMS surface properties for the long-term ESC culture and enhanced ESC myocardial differentiation. Following the establishment of coating strategy, the influence of PDMS substrate stiffness on ESC pluripotency maintenance and cardiac differentiation was further investigated. Different PDMS substrates exhibited different profiles of substratum properties, which affected the behaviors of ESCs and EBs on PDMS surfaces. ESC adhesion and proliferation, as well as EB attachment, were improved on the 40:1 PDMS substrate as compared to the other PDMS substrates. Meanwhile, compared with the other PDMS substrates, ESC pluripotency preservation was improved on the 5:1 PDMS substrate, while the 40:1 PDMS substrate encouraged ESC cardiac differentiation. These results were successfully applied in fabrication of biochips for ESC pluripotency maintenance and cardiac differentiation. The use of this simple surface modification strategy to stabilize the adhesion of ESCs and EB while enhance their pluripotency and differentiation, as well as substrate stiffness optimization, can possibly contribute to the development of a real heart-on-a-chip for high throughput drug screening in the future. Finally, the effects of pore density and pore sizes on hydrogel vascularization were studied both in vitro and in vivo. An increase of pore density greatly enhanced the proliferation and endothelial differentiation of encapsulated EPOCs in Gel-MCG constructs. In particular, compared to MS:Gelatin (1:1) counterpart, MS:Gelatin (2:1) constructs with higher pore density allowed the interconnected vascular network formation within the whole constructs upon the degradation of thinner gel walls among neighboring pores. Extensive vascular invasion was observed within the MS:Gelatin (2:1) constructs when implanted in vivo. These findings demonstrated that the vascularization of Gel-MCG constructs could be improved by increasing cavitary density. The effects of pore sizes on hydrogel vascularization by EPOCs were also evaluated in vitro and in vivo. Differentiation of EPOCs and hydrogel vascularization were promoted by middle pores as compared to large or small pores. When implantation in vivo, hydrogels with large pores induced more red blood cell-containing vessels and vascular tissues than hydrogels with small or middle pores. These results indicated that middle pores promoted hydrogel vascularization in vitro, while hydrogel vascularization in vivo was improved by large pores. These studies revealed the importance of pore densities and pore sizes in hydrogel vascularization both in vitro and in vivo and these findings can help design an optimal pore density and size for hydrogel constructs to enhance their vascularization. In summary, the studies in this thesis prove that physical signals can be utilized to improve performances of tissue engineered constructs. By utilization of physical signals from cells, we develop a new tool to monitor ESC viability during EB development to screen EBs with homogenous sizes and vascularize chondrocyte-derived cartilage templates with hypertrophic induction. Through manipulation of stiffness and topographic cues pf biomaterials, we improve efficiency of ESC cardiac differentiation and hydrogel vascularization.